Band gap engineered Sn-doped bismuth ferrite nanoparticles for visible light induced ultrafast methyl blue degradation. Issue 24 (15th December 2022) - Chakraborty, Sonam; Chakraborty, Nirman; Mondal, Swastik; Pal, Mrinal
Abstract: Remediation of water pollution persists as major concern for scientists and industry. Various ceramic based nanomaterials have been used in efficient photocatalytic degradation of different industrial dyes. However, the major factors that restrict efficacy of these systems are requirement of UV source for activating dye degradation process, prolonged time for degradation and lower efficiency. This paves way to development of alternative material systems that can resolve above problems by not only ensuring maximum dye degradation in minimum time in presence of visible light but also reusability in several cycles. In this work, we report visible light driven photocatalytic degradation of methyl blue (MB) using Sn-doped bismuth ferrite (BFO) nanoparticles. Different concentrations (0, 1%, 1.5%, 2%) of Sn-doped BFO nanoparticles were synthesized using facile sol-gel methods. It was observed that 1.5% Sn-doped BFO nanoparticle exhibits highest photocatalytic activity towards MB degradation compared with pure and other doped BFO nanoparticles. 1.5% Sn-doped BFO nanoparticle delineates 70% dye degradation capability within 10 min of irradiation under visible light. 1.5% Sn-doped sample shows 99% degradation capability within 2 h of visible light irradiation while pristine BFO nanoparticles can degrade only 20% under identical conditions. Additionally, 1.5% Sn-doped BFO nanoparticles are also capable of degrading RhB, another important contaminant. The 1.5% Sn-doped BFO nanoparticle could be a promising photocatalyst for efficient degradation of industrial effluents having various dyes. The efficient dye degradation of 1.5% Sn doped BFO nanoparticle has been explained in terms of increased density of surface active sites evident from bulk structural analyses and greater probability of generation of electron-hole pairs on surface by virtue of reduced band gap. A theoretical modelling of band structure has been done to identify surface . OH ions as most effective species to promote dye degradation. Highlights: Visible light induced methyl blue (MB) degradation using Sn-doped BFO nanoparticles. 1.5% Sn-doped BFO nanoparticles can degrade 70% MB within 10 min. Improved dye degradation efficiency by 1.5% Sn-doped BFO nanoparticles is due to increase in electron-hole generation rate because of reduced band gap. Increased concentration of surface active sites in BFO due to decrease in unit cell volume by virtue of Sn doping. Langmuir-Hinshelwood model was used in explaining the kinetics of photo-degradation.